STRATEGIES FOR USING PBL MODEL WITH A SCIENTIFIC APPROACH TO IPAS SUBJECTS TO IMPROVE STUDENTS' LEARNING OUTCOMES - siti hardiyanti hastuti; ocha estiani; mizannur; risa perwita sari (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lampung, 2025)
Multicultural education in Indonesia is very important in building awareness of tolerance and diversity in a diverse society. This research uses a literature review method to explore the urgency of multicultural education as an effort to prevent social conflicts that often occur due to differences in ethnicity, religion and race. Through analysis of various literary sources, it was found that multicultural education not only teaches about cultural diversity, but also instills values of mutual respect and tolerance among students. This research shows that implementing comprehensive multicultural education in schools can help students understand and appreciate differences, and prepare them to live side by side in harmony. With this, multicultural education is an essential strategy in building a society that is tolerant and respects diversity in Indonesia.